The Forms of Fluoride in Antarctic Krill (Euphausia superba) Oil Extracted with Hexane and its Removal with Different Absorbents. Issue 7 (9th August 2017) - Yin, Fa-Wen; Zhou, Da-Yong; Liu, Yan-Fei; Zhao, Qi; Zhou, Xin; Song, Liang; Qin, Lei; Qi, Hang; Zhu, Bei-Wei
ABSTRACT: Krill oils (KOs) were prepared using different extraction methods (hexane and supercritical carbon dioxide), different materials (heat-dried krill powder, freeze-dried krill powder, and freeze-dried krill tail meat powder), and different standing times during hexane extraction. The fluoride concentrations in the KOs were positively correlated with the protein concentrations. Absorbents were employed to remove fluoride from KO. Activated clay achieved the highest fluoride removal rate (70.66%), followed by calcium oxide (14.49%), activated carbon (11.97%), calcium chloride (9.32%), activated alumina (0.94%), and chitosan (0.52%). Meanwhile, the protein removal rates of the above absorbents were positively correlated with the fluoride removal rates.